Future Pain at the Diesel Pump? Potential Effects of the European Commission's Energy Taxation Proposal - Manuel Frondel; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
The Energy Tax Directive recently proposed by the European Commission envisages to tax fuels based on their energy content. By raising prices for diesel to a level higher than that of petrol, this proposal would eliminate the price advantage currently enjoyed by diesel in most EU Member States. To explore the implications of such a tax regime for automobile travel, the present analysis undertakes a comparative analysis of price elasticities for both fuel types. Drawing on household panel data from Germany, we fail to reject the hypothesis that the fuel price elasticities for petrol and diesel are equal. With our uniform fuel price elasticity estimates being on the order of -0.5 to -0.42, the typical finding from the empirical literature that the elasticities gleaned from household-level data are generally larger than those from aggregate time-series data is reconfirmed.
Keywords: L98; Y10; 330; Fuel taxation; fuel price elasticities; household data; automobile travel; panel